MODEL DIFRAKSI SINYAL PADA BIDANG MIRING TAJAM - suhartono, Suahrtono; Kushartantya, Kushartantya; sugiharto, Aris (MATEMATIKA, 2008)
Signal is a wave that can be expressed by physical phenomenon. Mathematically signal wave can be represented as a function of single or many independent variables, for example signal wave over hill or mountain as a function of distance or time. In fact, signal spreading as a wave have many attenuation, for example is caused by difractionÂ when the signal over hill or building. The purpose of this writing scientific jurnal is to make a model of knife edge difraction, that seen by two cases, such as transmitter has same height to receiver and transmitter has different height to receiver. Computation result show that transmitter has same height to receiver then the increasing of value of v cause reduction of difraction variable. AndÂ in case of the height transmitter and receiver is not the same, the degradation of v variable has an effect to the increasing of difraction variable. Â